PERANCANGAN RANGKAIAN SEDERHANA INFANT WARMER BERBASIS ARDUINO UNO MENGGUNAKAN SIMULASI WOKWI - Muwaffaq, M.Rifqi (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2024)
Adjusting the temperature of a newborn baby to room temperature is a problem that often occurs, 34 to 37°C is the baby's temperature while in the womb. For this problem, a tool was created, namely an infant warmer. An infant warmer is a medical device specifically designed for comfort and warmth for newly born babies. And it is equipped with several features, such as a temperature sensor and automatic temperature control. This tool makes it easier for medical professionals to observe the baby's condition. And it can reduce the risk of hepotemia (low body temperature) in babies, which has a bad impact on the baby's health. In this infant warmer series, we use an Arduino Uno controller to display on an I2C Liquid Crystal Display (LCD) with 2x16 characters, using a relay as a replacement for the infant warmer heater, DHT22 is used for the room temperature sensor, and LED as a marker for maximum and minimum temperature limits. From the Wokwi simulation it can be simulated smoothly according to the design and expected events.